Advice-Taking for Objective Face Age Estimates Relative to Subjective Face Trustworthiness Estimates - Joseph R. Phillips; Gabrielle Weidemann; Natalie C. Ebner; Phoebe E. Bailey (Behavioral Sciences, 2025)
This study examined whether advice-taking differs when making subjective face trustworthiness estimates relative to objective face age estimates. Participants (N = 177) completed a judge–advisor system task to measure how much weight they would give to advice regarding the age of a face (i.e., an objective estimate with a single correct answer) versus the trustworthiness of a face (i.e., a subjective estimate without a correct answer). Measures of fluid intelligence and working memory assessed cognitive resources, and participants provided ratings of perceived difficulty and confidence for each type of estimate. The difference between initial estimates and advice provided a measure of actual difficulty for each type of estimate. We found that advice-taking was greater when estimating face age than face trustworthiness. In addition, perceived difficulty, confidence, and actual difficulty were greater for face trustworthiness than age estimates. However, greater advice-taking was associated with greater actual difficulty for face age estimates, and less actual difficulty for face trustworthiness estimates. While previous research suggests that advice-taking increases with task difficulty, the current data reveal that this may depend on type of estimate. Subjective trustworthiness estimates that were more difficult to estimate than objective age estimates were associated with less advice-taking, and this may be at least partly attributable to differing motivations underlying objective (age) vs. subjective (trustworthiness) estimations.